Electromagnetic signal transformation in nonstationary plasma at temporary jump of external magnetic field - Nerukh, A.G.; Khizhnyak, N.A. (Вопросы атомной науки и техники, 2000)
Electromagnetic wave transformation in plasma with a slowly changing external magnetic field has been considered in reference [1] and in suddenly formed plasma in the steady-state external magnetic f ield in [2,3]. In this work the electromagnetic transformation with changing in time both the external magnetic field and plasma density have been considered. Temporary changes of the magnetic field and plasma density are approximated by a succession of step functions. The field transformation for each temporal step is exactly defined by Volterra’s integral equation solution describing the magnetic field in magnetized plasma.